KEPEMILIKAN INSTITUSIONAL MEMODERASI CORPORATE SOCIAL RESPONSIBILITY DAN KOMPENSASI EKSEKUTIF TERHADAP AGRESIVITAS PAJAK - Anisa Nurmaharani, (2022)
The purpose of this study is to examine the corporate social responsibility and executive compensation on tax aggressiveness moderated by institutional ownership with profitability and leverage as controlling variables. Tax aggressiveness is proxied using the book tax difference formula. Corporate social responsibility is measured using a logarithm, executive compensation using a natural logarithm, institutional ownership by comparing institutional shares with outstanding shares, profitability using the return on assets ratio, and leverage using the debt to asset ratio. The objects in this study are all company sectors listed on the Indonesia Stock Exchange except for the financial sector in 2019-2020. The sample was selected using a purposive sampling technique so that the sample obtained was 178 samples. The software used to test the hypothesis is STATA version 16. The results of this study indicate that 1) corporate social responsibility has no significant effect on tax aggressiveness; 2) executive compensation has no significant effect on tax aggressiveness; 3) Institutional ownership does not moderate corporate social responsibility towards tax aggressiveness; 4) Institutional ownership does not moderate executive compensation for tax aggressiveness.